Essential Roles for Mannose-Binding Lectin-Associated Serine Protease-1/3 in the Development of Lupus-Like Glomerulonephritis in MRL/lpr Mice - Machida, Takeshi; Sakamoto, Natsumi; Ishida, Yumi; Takahashi, Minoru; Fujita, Teizo; Sekine, Hideharu (Frontiers in Immunology, 2018)
The complement system, composed of the three activation pathways, has both protective and pathogenic roles in the development of systemic lupus erythematosus (or lupus), a prototypic autoimmune disease. The classical pathway contributes to the clearance of immune complexes (ICs) and apoptotic cells, whereas the alternative pathway (AP) exacerbates renal inflammation. The role of the lectin pathway (LP) in lupus has remained largely unknown. Mannose-binding lectin (MBL)-associated serine proteases (MASPs), which are associated with humoral pattern recognition molecules (MBL or ficolins), are the enzymatic constituents of the LP and AP. MASP-1 encoded by the Masp1 gene significantly contributes to the activation of the LP. After the binding of MBL/ficolins to pathogens or self-altered cells, MASP-1 autoactivates first, then activates MASP-2, and both participate in the formation of the LP C3 convertase C4b2a, whereas, MASP-3, the splice variant of the Masp1 gene, is required for the activation of the zymogen of factor D (FD), and finally participates in the formation of the AP C3 convertase C3bBb. To investigate the roles of MASP-1 and MASP-3 in lupus, we generated Masp1 gene knockout lupus-prone MRL/lpr mice (Masp1/3−/− MRL/lpr mice), lacking both MASP-1 and MASP-3, and analyzed their renal disease. As expected, sera from Masp1/3−/− MRL/lpr mice had no or markedly reduced activation of the LP and AP with zymogen forms of complement FD. Compared to their wild-type littermates, the Masp1/3−/− MRL/lpr mice had maintained serum C3 levels, little-to-no albuminuria, as well as significantly reduced glomerular C3 deposition levels and glomerular pathological score. On the other hand, there were no significant differences in the levels of serum anti-dsDNA antibody, circulating ICs, glomerular IgG and MBL/ficolins deposition, renal interstitial pathological score, urea nitrogen, and mortality between the wild-type and Masp1/3−/− MRL/lpr mice. Our data indicate that MASP-1/3 plays essential roles in the development of lupus-like glomerulonephritis in MRL/lpr mice, most likely via activation of the LP and/or AP.